Analisis Praktik Klinik Keperawatan pada Pasien St Elevation Myocardial Infarction (STEMI) dengan Intervensi Inovasi Terapi Musik Mozart Kombinasi Eye Mask untuk Peningkatan Kualitas Tidur Pasien di Ruang ICCU RSUD Taman Husada Bontang - Wahyuni, Wahyuni; Herlina, Nunung; Septiawan, Taufik; Astuti, Zulmah (Poltekkes Kemenkes Yogyakarta, 2024)
Heart disease is the leading cause of death worldwide. Approximately 17.5 million people die each year from heart disease, accounting for a significant portion of global mortality. One of the common heart diseases in Indonesia is ACS, or acute coronary syndrome. A complete blockage of a specific coronary blood vessel results in STEMI, which completely stops blood flow and prevents the heart muscle from receiving oxygen and nutrients, ultimately leading to its death. This research aims to improve sleep quality in patients with ST elevation myocardial infarction. (STEMI). The implementation of the innovative Mozart music therapy intervention, in conjunction with an eye mask, resulted in a slight improvement in the patient's sleep pattern quality. Based on the client's observation, the patient achieved a PSQI score of 8. (kualitas tidur klien buruk). From the innovations carried out, it can be concluded that Mozart music therapy is effective in improving the sleep quality of patients, but not significantly, as the score from the post-intervention results of Mozart music initially was 11 and became 8 after 3 days of intervention, indicating that the patients' sleep quality remains poor since the change in score is minimal and not very significant.